2007
DOI: 10.1111/j.1469-8749.2007.02007.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum fever and chorioamnionitis as risks for encephalopathy in term newborns: a case–control study

Abstract: In this study we examined the relationship between diagnoses of isolated intrapartum fever or chorioamnionitis and the risk of encephalopathy in term newborns. We conducted a populationbased, case-control study in Washington State using 1994 to 2002 linked data from the Washington State Birth Registry and the Comprehensive Hospital Abstract Reporting System (CHARS). We identified 1060 singleton, term newborns (602 males, 458 females) with International Classification of Diseases (ICD-9) diagnoses consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 27 publications
1
55
1
1
Order By: Relevance
“…In addition, clinical chorioamnionitis was associated with a more than fivefold increased risk of neonatal encephalopathy by Blume et al 29 in a retrospective, population-based study; however, histological findings were not reported. A recent study from the Netherlands examined the associations between placental pathology and the patterns of brain injury, as detected by magnetic resonance imaging (MRI), amongst term-born infants diagnosed with neonatal encephalopathy.…”
Section: Observations On Placental Pathologymentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, clinical chorioamnionitis was associated with a more than fivefold increased risk of neonatal encephalopathy by Blume et al 29 in a retrospective, population-based study; however, histological findings were not reported. A recent study from the Netherlands examined the associations between placental pathology and the patterns of brain injury, as detected by magnetic resonance imaging (MRI), amongst term-born infants diagnosed with neonatal encephalopathy.…”
Section: Observations On Placental Pathologymentioning
confidence: 94%
“…28 Neither maternal fever nor clinical chorioamnionitis has been found to accurately predict histological findings. 29 In its severest form, membrane inflammation involves the cord (funisitis), with vasculitis of the umbilical vessels and the presence of fetal neutrophilic granulocytes indicating activation of the fetal inflammatory response. Fetal inflammatory responses have been associated with neurological impairment in both term-born and preterm infants.…”
Section: Clinical Observations On Inflammation-induced Sensitization mentioning
confidence: 99%
See 1 more Smart Citation
“…Cases were not excluded from classification as IPR if the criteria for infection were met, because clinical observations for infection were made after childbirth, during the first home visit, and we desired to characterize the potential interaction between neonatal infections and intrapartum hypoxia in the development of NE. [15][16][17] We further ascertained the subset of cases of probable IPR NRD that progressed to NE. NE was defined on the basis of neurologic abnormalities observed in the first 7 days of life (seizures or 2 of the following: lethargy, poor suck, or respiratory depression, defined as a respiratory rate of Ͻ40 breaths per minute, as measured by the study worker).…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, this is the first population-based estimate of the incidence of NE from a community-based cohort in a developing country. With the assumption of a 30% disability rate among survivors of NE, 16,17 the impair- (14) 42 (10) 12 (11) 1385 (7) Hypoxic-ischemic intrapartum events may contribute to 30% to 80% of cases of NE. 30,[35][36][37] In Perth, Australia, 30% of NE cases had evidence of intrapartum hypoxia, defined on the basis of abnormal fetal heart rates, meconium staining, and low Apgar scores.…”
Section: Figurementioning
confidence: 99%